Biologically based method for the synthesis of Hg–Se nanostructures by Shewanella spp. Issue 27 (23rd February 2015) - Ho, Cuong Tu; Nguyen, Anh-Tuyet; Duong, Thi-Thuy; Le, Thi-Phuong-Quynh; Dang, Dinh-Kim; Tang, Thi-Chinh; Hur, Hor-Gil
Abstract : Living organisms, especially microorganisms, have the potential to offer cheap and benign synthetic routes for the production of nanomaterials. Abstract : Living organisms, especially microorganisms, have the potential to offer cheap and benign synthetic routes for the production of nanomaterials. In this study, we demonstrated the formation of various Hg–Se nanostructures by a combinatory method with the major participation of Shewanella bacteria. The quantum dots of Hg–Se were produced and located on the membrane surface of Shewanella cells by incubating the Shewanella putrefaciens 200 with Hg(ii ) and Se(iv ) under anaerobic conditions. The selenium nanowires and stellated polyhedral structures, successfully synthesized by Shewanella -mediated formation in 80 and 90% of DMSO, were used as templates for the formation of Hg–Se nanowires and stellated polyhedral structures. The liquid mercury was directly reacted with Se nanowires or stellated polyhedral structures in water and coated the Se nanostructures to form the core–shell structures of Hg–Se after 12 hours incubation at ambient temperature. SEM, TEM, XRD and EDX were used to characterize and confirm the Hg–Se nanoparticles and nanowires or stellated polyhedral structures.